Urban human needs: conceptual framework to promoting urban city fulfills human desires - Alsayed, Shaimaa S. (Frontiers in Sustainable Cities, 2024)
Cities have been created to meet human needs, but creating sustainable societies has become a major challenge in light of the planners' broad interest in creating smart cities or giving exclusive priority to the environmental dimension of sustainability. This is one of the goals related to sustainable development (SDGs) and therefore, the human perspective of urbanism is considered a future challenge in achieving (SDGs) . The research aims to bridge the gap in previous studies and highlight the integration of human needs in plans for urban human cities (UHN). It also aims to create a conceptual framework that leads to a new theory of urban needs by Bridging the knowledge gap in previous studies by considering modern numerical analysis tools, Thus, a bibliometric analysis based on the Biblioshiny and VOSviewer tools within the scope of human needs and urban cities promotion was accomplished. Next Selecting evaluation criteria for human needs through a comparative critique of the most important theories of human needs .Then Deducting the new theory of urban needs (HUN) and linking it to the elements of urban composition. Results have reached a new framework that clarifies the human needs that need to be achieved and links them to the urban components to create an integrated urbanization that fulfills the desires of the population. This research serves as a reference for reevaluating urban directions and modern theories that aim to develop future cities. It also helps evaluate cities, envision future human needs, and achieve future prosperity for cities.